Critical success factors for adopting green supply chain management and clean innovation technology in the small and medium-sized enterprises: A structural equation modeling approach - Maqsood, Shoaib; Zhou, Yan; Lin, Xintong; Huang, Shuai; Jamil, Ihsan; Shahzad, Khurram (Frontiers in Psychology, 2022)
The organization sustainability in the form of environmental management and sustainable production is becoming more important for small and medium-sized enterprises (SMEs) throughout the world. This research evaluates the factors affecting to understanding the CEO’s /Mangers intension to adopt the practices of green supply chain management (GSCM) and clean innovation technology (CIT)in the manufacturing SMEs of Pakistan. The empirical research identifies key determinants influencing the adaptation of GSCM practices. By using the approach of structural equation modeling (SEM), we selected a sample size of 350 different manufacturing firms in Pakistan. The results of the study reveal that six factors, namely, environmental, government, organization, suppliers, market, and operational factors, significantly influence the intention to adopt the GSCM and positively impact on sustainable production. The study findings reveal that market and operational factors are highly significant for adopting the GSCM practices at a p value of “0.05”. The environmental and organizational factors are also strongly significant to adopt the GSCM practices at the p value of “0.10”.This research also analyzes the CIT as a moderator with the association among environmental, government, organization, customer, supplier, economic, market, and operational factors in the context of Pakistan. The hypotheses H9a, H9b, h9f, and H9g are all good and support the use of CIT to boost the enterprise production and consumption. The research findings help policymakers understand how to implement GSCM practices and help enterprises implement GSCM and CIT practices for enterprise performance and environmental sustainability.